How cations determine the interfacial potential profile: Relevance for the CO2 reduction reaction. (10th December 2019) - Hussain, Ghulam; Pérez-Martínez, Laura; Le, Jia-Bo; Papasizza, Marco; Cabello, Gema; Cheng, Jun; Cuesta, Angel
Abstract: The strong effect of the electrolyte cation on the activity and selectivity of the CO2 reduction reaction (CO2 RR) can only be understood and controlled if the cation's effect on the interfacial potential distribution is known. Using CO (the key intermediate in the CO2 RR) adsorbed on Pt as a probe molecule, and combining IR spectroscopy, capacitance measurements and ab initio molecular dynamics, we show that the cation size determines the location of the outer Helmholtz plane, whereby smaller cations increase not just the polarisation but, most importantly, the polarizability of adsorbed CO (COad ) and the accumulation of electronic density on the oxygen atom of COad . This strongly affects its adsorption energy, the degree of hydrogen bonding of interfacial water to COad and the degree of polarisation of water molecules in the cation's solvation shell, all of which can deeply affect the subsequent steps of the CO2 RR. Graphical abstract: Image 1